Factores de riesgo psicosocial en trabajadores de una cooperativa de acuerdo a características sociodemográficas y condiciones intralaborales (2021)
This research analyzed the psychosocial risk factors of 54 workers of a Cooperative whit site in the cities of Armenia Quindío, Pereira Risaralda and in the municipality of Cartago Valle del Cauca, according to sociodemographic characteristics and intralabor conditions; The above is proposed as a response to psychosocial risks occurring in the interactions of the organization, work management, environmental conditions, functions and needs of workers, which together come to exert harmful effects according to their perceptions and experiences, reducing initiative in decision making and control in the workload assigned.